Genomic similarity of carbapenem-resistant Enterobacterales collected from mothers and their neonates - Priyanka Basak; Sharmi Naha; Kirsty Sands; Subhajit Dutta; Suchandra Mukherjee; Bijan Saha; Timothy R. Walsh; Sulagna Basu (Journal of Global Antimicrobial Resistance, 2025)
Objective: New Delhi metallo-β-lactamase is endemic in India and the gut may act as a reservoir of carbapenemase-producing Enterobacterales (CPE). Maternal gut colonisation with blaNDM-harbouring CPE increases the risk of neonatal gut colonisation. This study aimed to assess the vertical transmission of CPE from pregnant mothers (rectal) to neonates (rectal and blood). Methods: Rectal samples were collected and processed for the presence of CPE, followed by bacterial identification and antibiotic susceptibility. Mother–neonate pairs colonised with the same species underwent pulsed-field gel electrophoresis and whole-genome sequencing to examine genetic relatedness. Detection of blaNDM variants and their transmissibility was performed. Results: Of the pregnant mothers (n = 86) and sick neonates (n = 93) analysed, eight mother–neonate pairs harboured similar carbapenem-resistant species, predominantly Klebsiella pneumoniae, followed by Escherichia coli. Pulsed-field gel electrophoresis and whole-genome sequencing revealed that most isolates from mother–neonate pairs were distinct and distributed within diverse sequence types, including epidemic clones (ST11/15/147/405/410). blaNDM-1/5/7 were detected in CPE and predominantly associated with conjugative IncFII and IncFII(K) replicons. Genomic analysis supported one case of vertical transmission (ST147; blaNDM-1-positive K. pneumoniae) from mother to a neonate. Further investigation of exogenous sources is required to understand the acquisition of bacteria. No evidence of transmission of blaNDM-harbouring plasmids within mother–neonate pairs carrying distinct isolates was observed, indicating the independent acquisition of bacteria. Conclusions: Although limited evidence of mother-to-neonate transmission was observed in this study, screening of the gut is necessary to understand CPE transmission in hospital settings and beyond. Targeted surveillance and infection-prevention policies are needed to curb CPE spread.